In vitro functionality and toxicity of dacarbazine delivery nanosystem for melanoma. - Almoussalam, Mousallam Mohammad (Cranfield University, 2018)
Dacarbazine (Dac) is a chemotherapeutic for melanoma. Its poor solubility, short half-life, and side effects limit its therapeutic use. Nanoparticles used as drug delivery systems (DDS) improve drug pharmacological properties, target site concentration, and stability. This study aimed to improve the therapeutic efficiency and decrease the systemic toxicity of Dacarbazine using nanostructured lipid carriers (NLC) for topical administration. Different NLC compositions were synthesised using a laboratory-based high sheer dispersion (HSD) method, and applying varying processes parameters. The preparations were optimized to achieve the desired NLC characteristics (average size 155±2 nm, polydispersity index (PDI) 0.1±0.05 and zeta potential -43.7±0.6) assessed using hydrodynamic light scattering (DLS), zetasizer and transmission electron microscopy (TEM). The optimized NLC (NLC/PI) were then used to encapsulate Dacarbazine. The resultant NLC/PI-Dac was characterized (average size 190±10 nm, PDI 0.2±0.03 and zeta potential -43.5 ± 1.2) and crystallinity determined using X-Ray Diffraction (XRD). The pharmacological properties of NLC/PI-Dac were then investigated and the percentage of encapsulation efficiency and drug loading capacity were determined to be 98.5±0.2% and 23.4±0.2%, respectively. The in vitro toxicity of NLC/PI-Dac was assessed using a melanoma cell line (A375). The in vitro drug release profile of NLC-Dac showed a biphasic pattern; 50% released over 2 hours and remainder within 30 hours. No toxicity was measured for the different NLC/PI concentrations after 24, 48 and 72 hours treatment, but there was an increase in toxicity of Dacarbazine after NLC/PI encapsulation (NLC/PI-Dac) at all concentrations and all-time points. NLC/PI and NLC/PI-Dac were stable in size, PDI and zeta potential when stored at 4°C for 3 months and the developed process was transferable to industrial-scale synthesis using the Micro Jet Reactor technique. NLCs were shown to be a suitable drug delivery system for Dacarbazine, achieving a desirable drug loading, encapsulation efficiency and drug release profile.
Keywords: Precirol; ATO-5; nanostructured lipid carriers; Dicarbazine; Micro jet reactor; melanoma